Peran Keluarga sebagai Fondasi Kesadaran Keagamaan Anak Usia Dini dalam Perspektif Pendidikan Islam - Nadia Trisnawati; Abdur Razaq; Kristina Imron (Journal on Education, 2024)
This research explains the role of the family in building religious awareness in young children. The literature evaluation indicates that a child's primary environment is their family. receive education. Moms and dads in the household are the first instructors in the development procedure of a child's life. The main task of the family is to create a building and atmosphere for the family education process so that it gives birth to a generation that is perceptive and has noble nature as a reliable foothold in a person’s life and jouney children. The results of theories that emphasize the value of family education as the initial foundation for children's education validate this reality. Islam ic religious education in earliest childhood years has a significant impact on how children develop their religious awareness. It is believed that the family is a child's first and most significant institution in forming their religious identity and character. The purpose of this study is to examine the part that families play in forming religious awareness in early childhood, with an emphasis on teaching Islam ic. Using a qualitative approach, this research collected data through in-depth interviews with parents and observations of religious practices in the family. The findings show that families have an important role in forming early childhood religious awareness through direct teaching, example, and a supportive family environment.